Rama sebagai penjaga kehidupan dalam relief Ramayana Prambanan - Hanggar Budi Prasetya; Wisma Nugraha Christianta (Universitas Gadjah Mada, 2016)
This study describes four reliefs of Ramayana Prambanan which depicts the event that Ade beenexperienced and performed by Rama as affirmation that he is the incarnation of Vishnu ―the god of thepreserver. The designer and sculptor of those reliefs considered that this event was important. Fromthe twenty-four of Ramayana’s relief panels, there are four relief panels which depict this event. Datawas collected by observing the entire Ramayana reliefs in Shiva temple and Brahma, in the Prambanancomplex. Relief was read by using the Flat Time Space (RWD) theory and compared with the textof the Old Javanese Ramayana (RJK). RJK text was used as a comparison, because the manufactureand the writings of RJK relief were made in the same period in nine centuries. It was conceivable thatboth of them were made from the same source. Based on the result, it can be concluded that the eventperformed by Rama asserts that he is the incarnation of Vishnu. As the incarnation of Vishnu, Rama isable to purify and to preserve life.